2022
DOI: 10.1177/09589287221101342
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards welfare and environmental policies and concerns: A matter of self-interest, personal capability, or beyond?

Abstract: In times of emergent emphases on how climate change will affect welfare societies, welfare policies and individuals’ welfare and vice versa, this study investigates public support for welfare and environmental policies and concerns. Since previous research and literature have pointed towards a socioeconomic divide between the welfare agenda and the environmental agenda in terms of public support, this article makes a thorough socioeconomic analysis of public welfare and environmental attitudes. The article ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…This literature, alongside early work on sustainable development (e.g. Brundtland, 1987), and climate justice work on procedural and recognition justice all provide insight into issues rasied under 3.2, however, with the exception of the work of Emilsson et al (2022) and Williams (2021) there has been limited work undertaken within social policy.…”
Section: Addressing Impacts Of Climate Change and Climate Policymentioning
confidence: 99%
“…This literature, alongside early work on sustainable development (e.g. Brundtland, 1987), and climate justice work on procedural and recognition justice all provide insight into issues rasied under 3.2, however, with the exception of the work of Emilsson et al (2022) and Williams (2021) there has been limited work undertaken within social policy.…”
Section: Addressing Impacts Of Climate Change and Climate Policymentioning
confidence: 99%
“…Men, people who are less well educated and those in more technical jobs are rather sceptical. Moreover, Emilsson (2022) found that eco-social policy tends to be supported by low and middle-income groups, whereas high-income groups prioritize environmental policies without considering social justice concerns.…”
Section: Previous Research Into Support For Eco-social Policymentioning
confidence: 99%
“…Previous research on attitudes to eco-social policy focused on individuals, and found that eco-social policy is more often supported by women, by politically left-oriented persons, persons with higher education and persons who hold universalistic values (Fritz and Koch, 2019; Otto and Gugushvili, 2020). Material self-interest also seems to play an important role, as ecological concerns are often trumped or crowded-out by competing needs to finance social benefits (Emilsson, 2022; Jakobsson et al, 2018). While such research into attitudes provides valuable knowledge about the personal determinants of certain opinions, there is also a risk that it will take on a behavioural perspective, suggesting how to educate or nudge individuals to ‘behave’ more sustainably; this ultimately shifts the responsibility for tackling climate change to individuals, and reproduces the neoliberal dogma of constant self-improvement.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the positive correlations observed with higher education levels, which tend to be consistently found, are interpreted through the lens of a 'capability perspective'. This perspective suggests that education and the resources it brings forth cultivate knowledge, concern, and efficacy that contribute positively to environmental attitudes and actions (Emilsson, 2022). Concerns with redistribution and fairness may also to some extent be important for citizens with higher levels of education, but here it is from a vantage point of material and cognitive surplus, in which there is no or little perceived trade-off between social concerns and environmental concerns (Fritz et al, 2021;Otto & Gugushvili, 2020).…”
Section: Socioeconomic Positionmentioning
confidence: 99%